STUDI KOMPARATIF PEMBOBOTAN KRITERIA AUDIT KINERJA AUDITOR BADAN PEMERIKSA KEUANGAN DENGAN PEMBOBOTAN MENGGUNAKAN METODE ANALYTICAL HIERARCY PROCESS (STUDI KASUS PADA INSPEKTORAT KABUPATEN KEPULAUAN TALAUD) - Lawitan, Iwan Bin; Karamoy, Herman; Poputra, Agus Tony (ACCOUNTABILITY, 2016)
This study aimed to recalculate the weighting of performance audit criteria by using Anlytical Hierarchy Process Method and comparing its results with the weighting of performance audit of Indonesian Supreme Audit Institution’s Auditor (BPK). Research conducted on Supervisory Apparatus Capability Model Government (APIP) at the Office of Inspectorate of Talaud Regency. This research is a descriptive qualitative-quantitative approach.Method of data collection with interviews, documentation and questionnaire. The results showed that in weighting of performance audit criteria, BPK’s auditor still use direct weighting and judgment, and there is a difference of percentage between performance audit criteria of BPK auditor and using AHP method. Keywords : Weighting, Performance Audit Criteria, AHP